Evaluation of thermal water leakeage impact in the Caiuá Aquifer in the presidente Epitácio/SP - Teramoto, Elias Hideo [UNESP]; Baessa, Marcus Paulus Martins; Chang, Hung Kiang [UNESP] (Lepidus Tecnologia, 2019)
Damages in a well casing of SAG located in the municipality of Presidente Epitácio/SP is releasing hot water to the shallow Caiuá Aquifer. The measured temperature of groundwater at the well is 70°C, possessing different hydrochemical and isotopic characteristics. Due to the uncertainties of the existence of leaks that allow water flow from the well to shallow aquifers, this work aimed to use stable isotopes, hydrochemical characterization and numerical models of flow and transport in order to evaluate the influence of the thermal water in the shallow aquifer Caiuá in the area of interest. The results suggest the groundwater near the thermal water well is isotopically and hydrochemically similar to the Guarani thermal water, possessing temperatures and anomalous physical-chemical characteristics for the Caiuá Aquifer. Numerical simulations indicate the flow of hot water from SAG well by continuous leakage is approximately 900 m3/day. These results indicate the existence of hot water flow from the thermal water well to the Caiuá Aquifer and the temperature rise is restricted to a few hundred meters around the leaking point.
Avaliação do impacto do vazamento de água termal do Aquífero Caiuá no munícipio de presidente Epitácio/SP
Keywords: Caiuá Aquifer; SAG; Stable isotopes; Thermal water